2012
DOI: 10.1002/cjoc.201100557
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Dendritic Hydroxyl‐terminated Cyanuric Chloride Derivatives and Their Properties

Abstract: Novel dendritic compounds G1.5(OH) 4 and G1.5(OH) 8 with peripheral hydroxyl were synthesized under mild conditions from cyanuric chloride, ethylene diamine, ethanolamine and diethanolamine. The products could be separated and purified through dispersion and precipitation in organic solvents with good yields (over 93.0%) and high purity (above 98.0%, HPLC). The structures of the products were characterized by IR, MS, 1 H NMR and elementary analysis. G1.5(OH) 4 and G1.5(OH) 8 could be dissolved in polar solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…The "temperature-controlled selectivity" and "functional groups selectivity" of triazine trichloride toward the nucleophilic substitution of chlorine atom was used throughout [20,28]. The first step was carried out at low temperature to ensure the substitution of single-chlorine atom of 2 moles of cyanuric chloride by 1 mole of piperazine [28] to give 1,4-biz(4,6-trichloro-1,3,5-triazin-2-yl)piperazine as a core for dendrimer synthesis. The product was purified by washing with acetone and methanol to remove unreacted cyanuric chloride and piperazine, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The "temperature-controlled selectivity" and "functional groups selectivity" of triazine trichloride toward the nucleophilic substitution of chlorine atom was used throughout [20,28]. The first step was carried out at low temperature to ensure the substitution of single-chlorine atom of 2 moles of cyanuric chloride by 1 mole of piperazine [28] to give 1,4-biz(4,6-trichloro-1,3,5-triazin-2-yl)piperazine as a core for dendrimer synthesis. The product was purified by washing with acetone and methanol to remove unreacted cyanuric chloride and piperazine, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…A few reports are available on the thermal properties of triazine-based dendrimer. Lin et al [28] reported the thermal stability of low-generation dendrimers with ethanolamine and diethanolamine groups on the periphery. Singh and Gupta [29] reported the thermal behavior of triazine-based dendrimer with triazine trichloride in core moiety and ester linkage on the periphery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present work, we have synthesized N,N'-biz (4,6-dichloro-1,3,5-triazin-2-yl)propane-1,3-diamine as core for dendrimer synthesis 28 . Dendrimer was then developed up to generation 3 using divergent method [29][30] .…”
Section: Research Articlementioning
confidence: 99%
“…[15,16] In chemical modification, PEG or MPEG could be improved via grafted, blocked, or cross-linked methods, [17] also many diverse properties can be acquired by designing various molecular chain structure. [18][19][20] Xi et al [21] reported a two-step procedure for preparing a novel polymer matrix solid-solid PCM. Li et al [22] reported that PEG/MDI/PE tertiary cross-linking copolymer had high enthalpy of 152.97 J/g and suitable transition point at 58.68 ℃.…”
Section: Introductionmentioning
confidence: 99%